Design and construction of a compact, high-repetition-rate ultrafast electron diffraction instrument - Freelon, Byron; Rohwer, Timm; Zong, Alfred; Kogar, Anshul; Zhou, Hengyun; Wong, Liang Jie; Ergeçen, Emre; Gedik, Nuh (Review of scientific instruments, 2023)
We present the design and performance of a compact ultrafast electron diffraction instrument. The diffractometer provides a means of examining time-resolved ultrafast dynamical properties of solids. The system’s utilization is discussed in terms of instrument parameters and diffraction data from selected condensed matter samples. The difractometer’s performance is highlighted in terms of detection sensitivity, instrumental temporal resolution, and the electron beam transverse coherence length. Following specific details of the construction, we present a practical discussion of parameters such as repetition rate and provide advice on general construction approaches for laboratory-based, keV ultrafast electron diffractometers. In addition, design guidance for constructing a compact electron gun source that is well-suited for studying diffraction from hard condensed matter is given. A unique data acquisition scheme, utilizing high laser repetition rates, is presented.